Review of Hygrogeus Mulsant & Rey, 1880 and Trichodromeus Luze, 1903, with descriptions of three new genera from the eastern Palaearctic Region (Coleoptera: Staphylinidae: Anthophagini: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2024)
Five genera of the “Hygrogeus” complex of the omaliine tribe Anthophagini Thomson, 1859 are (re-)described and illustrated: Hygrogeus Mulsant & Rey, 1880, Trichodromeus Luze, 1903, Asiageodromicus gen. n., Himalodromeus gen. n. and Microhygrodromicus gen. n. The genus Hygrogeus contains three species: H. aemulus (Rosenhauer, 1847), known from the Middle European Alps, and two species with uncertain generic status from Kashmir: H. minor Coiffait, 1983 and H. rugosicollis Coiffait, 1983. The genus Trichodromeus contains 21 species distributed in the eastern Palaearctic Region. Four species of Trichodromeus are (re-)described and illustrated: T. kumaonensis (Champion, 1925) (India), T. ketmeniensis (Bordoni, 1985) (Kazakhstan, Kyrgyzstan, Turkmenistan), T. penicillatus (Reitter, 1900) (Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan), and T. telnovi sp. n. (Nepal). A new synonymy is established: T. ketmeniensis = T. ovchinnikovi Shavrin & Klimenko, 2008 syn. n. Eight new combinations are proposed: T. alticola (Coiffait, 1983) comb. n. (from Hygrogeus), T. chinensis (Cheng & Peng, 2019) comb. n. (from Hygrogeus), T. gulmargensis (Coiffait, 1983) comb. n. (from Hygrogeus), T. languidus (Coiffait, 1983) comb. n. (from Hygrogeus), T. longipalpis Coiffait, 1983 comb. n. (from Geodromicus Redtenbacher, 1857), T. meurguesae Coiffait, 1979 comb. n. (from Hygrogeus), T. montanus (Coiffait, 1983) comb. n. (from Hygrogeus), and T. sulcicollis (Coiffait, 1983) comb. n. (from Hygrogeus). The habitus of T. pusillus (Coiffait, 1983), and habitus and aedeagi of T. armatus (Cameron, 1941) and T. jaegeri Shavrin, 2021 are illustrated. The genus Asiageodromicus gen. n., distributed mainly in the Himalayan Region and Tibet, contains nine species. Eight species of them were previously attributed to the crassipalpis group (Shavrin 2019) of Geodromicus: A. amplissimus (Shavrin, 2019) comb. n., A. crassipalpis (Champion, 1920) comb. n., A. dolpoensis (Coiffait, 1982) comb. n., A. namucoicus (Cheng & Peng, 2020) comb. n., A. palpalis (Coiffait, 1977) comb. n., A. spadiceus (Shavrin, 2019) comb. n., A. subquadratus (Cheng & Peng, 2020) comb. n., and A. trapezipennis (Coiffait, 1979) comb. n. Two species are (re-)described and illustrated: A. dolpoensis and A. weiperti sp. n. (eastern Nepal). The Himalayan genus Himalodromeus gen. n. contains three species. All these species are (re-)described and illustrated: H. cyanipennis (Cameron, 1924) comb. n. (from Hygrogeus), known from India and Nepal, H. grandis sp. n. (Pakistan) and H. reductus sp. n. (Nepal). A new synonymy is proposed: H. cyanipennis = Hygrogeus coeruleipennis Coiffait, 1983 syn. n. Lectotypes for Hygrogeus cyanipennis Cameron, 1924 and Hygrogeus cyanipennis atrocaeruleus Champion, 1925 are designated. The genus Microhygrodromicus gen. n. contains two new species from Yunnan (China): M. exiguus sp. n. and M. politus sp. n. Keys for genera of the “Hygrogeus” complex, all species of Asiageodromicus gen. n., Himalodromeus gen. n. and Microhygrodromicus gen. n. are provided. Distributional maps of T. jaegeri Shavrin, 2021, T. ketmeniensis, T. penicillatus, T. telnovi sp. n., and all species of the new genera are given. Five species are recorded for the first time: A. crassipalpis, H. cyanipennis and T. jaegeri from Nepal, T. penicillatus from Uzbekistan and Kyrgyzstan, and T. pusillus from Pakistan.